Technological parameters for agroindustrial concern from seeds of Castilla pumpkin (C. moschata) and bitter pumpkin (A. undulata) - Martínez-Betancourt, Selena del Rocío (2023)
The objective of this work was to quantify either physical and chemical attributes of the whole along with grounded seeds from Castilla pumpkin (Cucurbita moschata Duchesne) and bitter pumpkin (Apodanthera undulata A. Grey). The parameters data for whole seeds of both pumpkin varieties were; physical dimensions, internal friction, external friction and particle size, while for their ground compound were; electric conductivity, soluble protein, total protein, carbohydrates, oil concentration and main minerals. Collected data is fundamental for generating technology for the productive processes and an aid for more efficient use of the entire organic mass, when new raw matter is obtained for separate processing areas, to diversify readily consumption produce and increasing productivity of agroindustrial mechanization. It was concluded that pumpkin crop raised all over this farming region offers an opportunity to build up agroindustrial innovative and technological processes. A comprehensive use of seeds with their skin has a significant advantage on the food industry. Therefore, the physical and chemical attributes are responsible for the selection of technical mechanization for the industrial swap processes, as well as all required gear and feedstock like water, minerals, energy and others within the add value chain to the original organic matter.